PENGARUH MOTIVASI DAN LINGKUNGAN TERHADAP MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI PADA SISWA SEKOLAH MENENGAH ATAS (SMA) DI KECAMATAN TANJUNG SAKTI KABUPATEN LAHAT - Zakiah . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
This study aims to analyze the influence of motivation and the environment on the interest of continuing studies to universities in high school students (SMA) in Tanjung Sakti Sub-district of Lahat Regency. Data analysis methods used are qualitative and quantitative, with primary and secondary data sources in the form of questionnaires, interviews, and documentation. The population in this study is all high school students in Kecamatan Tanjung Sakti, the sample used is purposive sampling with the number of samples as much as 100 respondents. The results showed that there is a significant influence of motivation and environment on the interest of continuing studies in high school students in Tanjung Sakti Sub-District Lahat simultaneously with a significance of 0.000. While partially both motivation and environment have an effect on interest to continue study where the significance of both of 0.000. Keywords: Motivation, Environment, Interest